2016
DOI: 10.1016/j.agrformet.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Correction for light scattering combined with sub-pixel classification improves estimation of gap fraction from digital cover photography

Abstract: and for calibrating and evaluating satellite remote sensing LAI products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…As was also noted by Hwang et al. (), photography on uniformly overcast days provided the greatest contrast between the canopy and sky.…”
Section: Resultssupporting
confidence: 66%
“…As was also noted by Hwang et al. (), photography on uniformly overcast days provided the greatest contrast between the canopy and sky.…”
Section: Resultssupporting
confidence: 66%
“…Typically, the quantification of UVC and OCC can be conducted by using nadir (downward-looking) and zenith (upward-looking) photography methods in the field, respectively [17]. Previous studies confirmed the effectiveness and accuracy of the commonly used photography methods [18,19] to segment green vegetation from the background (i.e., soil or sky). The ground-based measurement is generally treated as ground truth or reference value in validating other remote sensing estimates [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the field, if one alters the 512 camera exposure to gain contrast between leaf and woody elements, then the image is likely 513 to be over-exposed, leading to higher Pgap than from 'optimally' exposed images. Analternative to HP is to capture multi-angular images using narrow FOV digital cover 515 photography methods (Hwang et al, 2016;Macfarlane et al, 2007b;Macfarlane et al, 2014;516 Piayda et al, 2015). The comparatively higher image resolution over the same image sampling 517 domain has the advantage of being less sensitive to exposure (Blennow, 1995).…”
mentioning
confidence: 99%